Effect of corrosive media on galvanic corrosion of complicated tri-metallic couples of 2024 Al alloy/Q235 mild steel/304 stainless steel. Issue 9 (September 2019) - Shi, Linjun; Yang, Xiuying; Song, Yingwei; Liu, Dan; Dong, Kaihui; Shan, Dayong; Han, En-Hou
Abstract: Galvanic corrosion of tri-metallic couples is more complicated than that of bi-metallic couples. In this study, the effect of the pH of corrosive media on the galvanic corrosion of 2024 Al alloy/Q235 mild steel/304 stainless steel tri-metallic couples was investigated using potentiodynamic polarization, scanning electron microscopy, scanning vibrating electrode technique and a multi-channel galvanic corrosion meter. The results show that 2024 always acts as the only anode in 3.5 wt% NaCl at pH 5.56, 9.72 and 12.0, while both Q235 and 2024 act as anodes at pH 2.39 in the initial stage and then the role of Q235 changes at longer coupling time, which can be attributed to the effect of pH on the surface film of 2024. It is also found that the galvanic current density of a tri-metallic couple is the superposition of two bi-metallic couples when cathodic reactions are controlled by the diffusion of oxygen, otherwise it is smaller than that of the sum of two bi-metallic couples. The localized corrosion instead of uniform corrosion of anodic metal is accelerated by galvanic corrosion.